Persepsi Pemilih Pemula Pada Iklan Kampanye Politik(Studi Deskriptif Kuantitatif Persepsi Pemilih Pemula Di Kelurahan Karangmalang Pada Iklan Kampanye Politik Bupati Dan Wakil Bupati Kabupaten Sragen Tahun 2015) - Tyas, Wahyu Sumunaring, Drs. Joko Sutarso, S.E, M.Si (2017)
A political campaign advertisement is a rsuasive,structured, and non-personal communication containing goods, services, and also ideas spread widely through a media. All candidates coming from political partiestry to get support and good impression fromthe ctizens of the district of Sragen. A voters' Cognitive factor play important role to the voters to make their decisions, especiallyto the voters who have media literacy, as well as interest in political issues. Furthermore, popularity of political candidates determines the higher chances in gathering voters´ interest. It means that the more popular a political candidate is, the more chances he or she get to gain audience attention. This research applied descriptive quantitative method using questionnaires in order to gather the data. The samples of this research were 74 young voters. The data analysis used univariatetechnique.This result of the research showed that audience perception of young voters in Karangmalang village in the 2015 election from the aspects ofawareness,knowledge, liking, preference and conviction was very high. It showed that the perception of the young voters in the political campaign had made them know their own interest in ticipating the election. Even some voters agreed to participate in the election with their own awareness without any force from others.